PRESENTATION OF ORNAMENTAL FISH AND VISUALIZATION VARIOUS MAINTENANCE - Mohammed Sarifudin; Elly Agustina J, SKom, MMSI (Jurnal Sistem Informasi, 2006)
The development of increasingly sophisticated computer that is very helpful in data processing still using manual systems. This is often a problem associated with the accuracy of the data which resulted in delays in data processing.  Valuable information is the information quickly and accurately. Then needed a computerized application as a supporter. Visualization applications and maintenance of ornamental fish varieties in order to simplify the display data and images that objective.